Khazanah Ilmu Pengetahuan Kader HMI: Upaya Mempertahankan Nilai-Nilai Kebudayaan Lokal di tengah Arus Kebudayaan Modern - Mandar Ali (Ad-Dariyah: Jurnal Dialektika, Sosial dan Budaya, 2020)
Science is a tool for discovering and discovering truth within itself. But like it or not, the process must be passed by humans in earnest as a condition to reach absolute truth. In addition to finding, discovering and utilizing science as an effort to understand the verses of Allah SWT. Within the framework of maintaining and improving the way to seek knowledge is the logistical consequence of the role of the human caliphate. This caliphate became the basis of human creativity and innovation in various aspects without institutionalized knowledge and values.